ANALISA KINERJA KEUANGAN DAN PREDIKSI KEBANKRUTAN BANK PEMBIAYAAN RAKYAT SYARIAH - TONY ISWADI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. This study aims to assess the financial performance of existing BPRS in Central Sumatra, and predict the potential for bankruptcy in the BPRS. The method used to assess financial performance is to assess the performance of Capital, Efficiency, Liquidity and Profitability in the period of financial statements 2013-2015. While the potential for bankruptcy is done by using the Altman Z-Score method. The results showed that there were two potentially bankrupt BPRS.